Kinerja Struktur Perkerasan Aspal Porus Modifikasi dengan Pemodelan Program KENPAVE: Performance of Modified Porous Asphalt Pavement Structures Using the KENPAVE Program Modeling - Aszharri, Arief; Susetyo, Dimas Ariezky; Sulaiman, Suherman (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2024)
Flexible pavement planning methods can be classified into five categories, namely empirical methods, methods for limiting shear failure, methods for limiting deflection, regression methods based on pavement performance or road tests and empirical mechanistic methods. Pavement design procedures can be modeled as several layers or viscoelastic structures in an elastic band. By estimating that the pavement structure is like this, it is possible to calculate the stresses, strains, or deflections caused by traffic loads and environmental factors. This research will evaluate the construction structure of a porous asphalt mixture using cariphalte modified asphalt and the addition of gilsonite on a road section with a high traffic volume with an LHR above 50,000 pavement vehicles so that the thickness of the pavement structure layer will be obtained and then evaluated using the KENPAVE program. The results of this study show that the structural performance of porous asphalt mixtures with the addition of gilsonite in the pavement structure increases not significantly with increasing permit repetition loads at fatigue crack damage criteria of 0.5% and 0.45% for segment 4 and segment 5 respectively. Segment 3 showed a significant increase in the permit repetition load of 26.3% compared to the normal mixture. The structural performance of porous asphalt mixtures with the addition of gilsonite in the pavement structure increases insignificantly with the increase in the repetition permit load on the criteria for used grooves from vehicle wheels by 0.42% and 0.74% respectively for segment 4 and segment 5. However, in segment 3, there was a significant increase in the permit repetition load of 30.5% compared to the normal mixture.